(untitled) (Scientific journal of the Fergana State University, 2023)
Ulugbek Hamdam’s stories “Song about the Motherland” and “Pillapoya” are among the stories based on symbolism in the traditional psychoanalytic direction. The level of any artistic work, its artistry, the variety of image methods are determined by the sequence and believability of the development of events in it. In the artist’s story “Song about the Motherland”, we witness the intermingling of reality and the supernatural, and fairy-tale methods with fanaticism. It is noteworthy that in the stories of the artist, he reveals the current problems of today through philosophical ideas. The author’s stories are distinguished by the narrative style, harmony of form and content, and the combination of traditional and modernist style. The artist’s stories “Song about the Motherland” and “Pillapoya” are distinguished by the richness of the types of imagery used to describe the behavior of the characters. In the story “Song about the Motherland” , the love for the motherland, the sacrifices of our ancestors to their country, and the bravery of our ancestors are revealed through the image of the main character. In “Pillapoya” the harmony of material and spiritual life is described in bright images.